2004
DOI: 10.1158/0008-5472.can-03-3898
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Factor κB Subunits RelA/p65 and c-Rel Potentiate but Are Not Required for Ras-Induced Cellular Transformation

Abstract: Extensive data indicate that oncoproteins, such as oncogenic H-Ras, initiate signal transduction cascades that ultimately lead to the activation of specific transcription factors. We and others have previously demonstrated that Ras activates the inherent transcriptional activation function of the transcription factor nuclear factor B (NF-B). Supportive of the importance of NF-B in transformation, Ras-induced cellular transformation can be suppressed by expression of IB␣, an inhibitor of NF-B, or by dominant-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 47 publications
6
47
0
1
Order By: Relevance
“…This result is consistent with previous results showing that activation of kB-dependent reporter plasmids in response to Ras was inefficient in RelA-deficient cells (Finco et al, 1997). Moreover, while this work was in progress, Hanson et al (2004) also showed that mouse cells missing c-Rel, RelA, or both can be transformed by a human oncogenic Ras protein.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous results showing that activation of kB-dependent reporter plasmids in response to Ras was inefficient in RelA-deficient cells (Finco et al, 1997). Moreover, while this work was in progress, Hanson et al (2004) also showed that mouse cells missing c-Rel, RelA, or both can be transformed by a human oncogenic Ras protein.…”
Section: Discussionsupporting
confidence: 92%
“…For example, gene profiling has identified a subset of diffuse large B-cell lymphomas (the activated B-cell-like tumors) that requires NF-kB for growth and survival; in this case, the expression of genes associated with this type of lymphoma is blocked when NF-kB activity is inhibited (Lam et al, 2005). Similarly, in murine fibroblasts, oncogenic Ras expression regulates a set of approximately 25 genes in a manner dependent on NF-kB activity (Hanson et al, 2004). Interestingly, these studies also indicate that the NF-kB-controlled gene sets in distinct oncogenic settings are significantly different.…”
Section: Linking Nf-jb With Oncogenesismentioning
confidence: 83%
“…For instance, NF-kB is activated by both Her-2/Neu (ErbB2) and oncogenic H-Ras expression (Finco et al, 1997;Pianetti et al, 2001). Interestingly, in immortalized murine fibroblasts, oncogenic H-Ras requires the NF-kB subunits RelA and c-Rel for efficient cellular transformation (Hanson et al, 2004). In addition, activation of NF-kB by oncogenic Ras was reported to involve the IKK complex (Arsura et al, 2000; Figure 2).…”
Section: Activation By Oncoproteinsmentioning
confidence: 99%
“…Enhanced expression of the c-myc oncogene has been shown in Cr-transformed C3H/10T1/2 Cl8 mouse embryo cell lines [68], while the NF-(B subunit c-Rel has been shown to malignantly transform cells in culture [69,70]. Cr(VI) has been shown to both inhibit and activate the transcriptional activity of NF-(B [71,72], which may be related to differences in Cr concentration and cell type [73].…”
Section: Discussionmentioning
confidence: 99%